Bringing trust and transparency to the opaque world of waste management with blockchain: a Polkadot parathread application - Scott, Ian (2022)
Scott, Ian and de Castro Neto, Miguel and Pinheiro, Flavio L., Bringing Trust and Transparency to the Opaque World of Waste Management with Blockchain: A Polkadot Parathread Application (March 22, 2021). Available at SSRN: https://ssrn.com/abstract=3825072 or http://dx.doi.org/10.2139/ssrn.3825072